Measuring Palm Oil Mill Capacity Using Modelling and Simulation - Fazeeda, Mohamad; Razman, Mat Tahar (Universiti Malaysia Pahang, 2012)
This paper measured the capacity utilization of the palm oil mill operation system. The underutilized of capacity effect the production of the mill may disrupt the entire chain in the industry. Data were collected from a palm oil mill as the case study. Modelling and simulation were used in designing and accessing the mill operation using Arena simulation. The result will help the management to do better capacity planning towards effective supply chain management.